KINETICS AND MECHANISM OF PERMANGANATE OXIDATION OF CIPROFLOXACIN IN AQUEOUS SULPHURIC ACID MEDIUM (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The oxidation of ciprofloxacin (CIP) by permanganate ion in aqueous sulphuric acid medium at constant ionic strength (I = 0.05 mol dm-3) has been investigated spectrophotometrically at 525 nm. Order with respect to substrate, oxidant and acid concentrations were determined. Product characterization of reaction mixture indicates the formation of major product m/z 263 corresponding to dealkylation of the piperazine ring of ciprofloxacin. The piperazine moiety of ciprofloxacin is the predominant oxidative site to KMnO4. Product analysis indicates that oxidation of permanganate results in dealkylation at the piperazine moiety of ciprofloxacin, with the quinolone ring essentially intact. The reaction constants involved in different steps of the mechanism were calculated at different temperatures. The activation parameters with respect to the slow step of the mechanism were computed and thermodynamic quantities were also determined.